TESTS FOR PRINCIPLES. - Littleton, A. C. (The Accounting Review, 1938)
Abstract The article focuses on test for principles. The word principles has been extensively used by both accounting practitioners and academic writers with little discrimination in the context between the truths of accountancy and the practices of accountants. In a treatise for educational use, inclusiveness may be necessary so that accounting will be presented as a whole. But the student cannot be well trained in clear thinking unless the elements out of which the subject matter is constructed are clearly distinguished one from another. There is a growing movement, in the interest of clear thinking and orderly practice, toward the formulation of concise propositions regarding accounting. Each of these aspects is complementary to the other, and both need to be held in mind for true comprehension. But it is a task of some moment to classify numerous propositions as either rules or principles, for none of them can be both. To do so one needs more than dictionary definitions. A test by which to recognize a proposition as a statement of accounting principle is needed. Those propositions which do not meet the test may be useful statements of accounting rules.